Production, characterization and antioxidant activity evaluation of quercetin loaded PLGA nanofibers - Kaya, Secil; Derman, Serap (YILDIZ TECHNICAL UNIV, 2022)
Quercetin is a flavonoid which is known to have antioxidant, anticancer and antimicrobial activities and found high ratio in many plants and nutrients. As quercetin has a superior ability to scavenging of reactive oxygen species, its use in wound dressing studies is increasing. Electrospun membranes are seen to be advantageous in terms of controlled and continuous drug release, water absorption and mimicry to intercellular matrix elements. In this study, PLGA nanofibers are produced by electrospinning method. In their SEM images, it is observed that PLGA nanofibers are successfully produced with average diameter of 500 +/- 20 nm and they are bead-free and randomly. Quercetin was loaded onto the PLGA membrane by spraying method to ensure that the fibers were physically attached onto the surface. FTIR spectroscopy analysis showed that quercetin was successfully loaded onto the nanofibers. In the swelling study, it was found that water absorption capability of PLGA membrane is 300 +/- 30%. Drug release studies were performed with quercetin-loaded PLGA nanofibers and it was determined that quercetin was completely released in 7 days. Antioxidant activity of quercetin loaded PLGA nanofibers was tested by DPPH method and it was showed 85.1 +/- 0.8% antioxidant activity.
Keywords: Nanofibers; Electrospinning; Drug Loading Mechanism; Quercetin; ELECTROSPUN NANOFIBERS; CONTROLLED-RELEASE; DOXORUBICIN; MEMBRANES; DELIVERY; PLA; Engineering